Autoimmune Polyglandular Syndrome Type 3 with Anorexia - Toshio Kahara; Hitomi Wakakuri; Juri Takatsuji; Iori Motoo; Kosuke R. Shima; Kazuhide Ishikura; Rika Usuda; Yatsugi Noda (Case Reports in Endocrinology)
A 71-year-old man with diabetes mellitus visited our hospital with complaints of anorexia and weight loss (12 kg/3 months). He had megaloblastic anemia, cobalamin level was low, and autoantibody to intrinsic factor was positive. He was treated with intramuscular cyanocobalamin, and he was able to consume meals. GAD autoantibody and ICA were positive, and he was diagnosed with slowly progressive type 1 diabetes mellitus (SPIDDM). Thyroid autoantibodies were positive. According to these findings, he was diagnosed with autoimmune polyglandular syndrome type 3 with SPIDDM, pernicious anemia, and Hashimoto's thyroiditis. Extended periods of cobalamin deficiency can cause serious complications such as ataxia and dementia, and these complications may not be reversible if replacement therapy with cobalamin is delayed. Although type 1 diabetes mellitus with coexisting pernicious anemia is very rare in Japan, physicians should consider the possibility of pernicious anemia when patients with diabetes mellitus have cryptogenic anorexia with the finding of significant macrocytosis (MCV > 100 fL).